Functionalization of silica through thiol-yne radical chemistry: a catalytic system based on gold nanoparticles supported on amino-sulfide-branched silica. Issue 31 (9th March 2016) - Ballarin, Barbara; Barreca, Davide; Boanini, Elisa; Bonansegna, Elisa; Cassani, Maria Cristina; Carraro, Giorgio; Fazzini, Silvia; Mignani, Adriana; Nanni, Daniele; Pinelli, Davide
Abstract : Synthesis of a novel catalytic system based on gold nanoparticles supported on silica functionalized via a thiol-yne radical reaction. Abstract : This work proposes a preparation route to heterogeneous catalysts based on gold nanoparticles (AuNPs ) supported on chemically modified silica. More specifically, the latter is functionalized with amino-sulfide branches (Au-SiO2 @AeThio ) through a thiol-yne radical coupling performed between cysteamine hydrochloride and an alkynyl-substituted triethoxysilane, followed by co-condensation with tetraethoxysilane (TEOS). The target procedure, involving only a gold precursor without any need of additional reducing and/or stabilizing agents, is straightforward, controllable, reproducible, and particularly appealing from a "green" point of view. The supported AuNPs, with an average diameter of 10 nm, possess a remarkable catalytic activity (specific rate constants of the order of 10 −2 s −1 mgcat −1 ) in the reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) by sodium borohydride (NaBH4 ) in aqueous media. The higher performances with respect to previous literature work, along with the possibility of successfully recycling the catalyst, shows the developed materials as attractive functional platforms.